Pulmonary Madurella mycetomatis mycetoma secondary to knee eumycetoma, Senegal. - Khadim Diongue; Mamadou Alpha Diallo; Lamine Sarr; Mame Cheikh Seck; Ludivine Bréchard; Mouhamadou Ndiaye; Aida Sadikh Badiane; Stéphane Ranque; Daouda Ndiaye (PLoS Neglected Tropical Diseases)
Mycetoma is a neglected tropical disease which is endemic in Senegal. Although this subcutaneous mycosis is most commonly found on the foot, extrapodal localisations have also been found, including on the leg, knee, thigh, hand, and arm. To our knowledge, no case of blood-spread eumycetoma has been reported in Senegal. Here, we report a case of pulmonary mycetoma secondary to a Madurella mycetomatis knee eumycetoma. The patient was a 41-year-old farmer living in Louga, Senegal, where the Sudano-Sahelian climate is characterised by a short and unstable rainy season and a steppe vegetation. He suffered a trauma to the right more than 20 years previously and had received treatment for more than 10 years with traditional medicine. He consulted at Le Dantec University Hospital in Dakar for treatment of a right knee mycetoma which had been diagnosed more than 10 years ago. He had experienced a chronic cough for more than a year; tuberculosis documentation was negative. Grains collected from the knee and the sputum isolated M. mycetomatis, confirmed by the rRNA gene ITS regions nucleotide sequence analysis. An amputation above the knee was performed, and antibacterial and antifungal therapy was started with amoxicillin-clavulanic acid and terbinafine. The patient died within a month of his discharge from hospital.